Recent Advances in Mathematical Research and Computer Science Vol. 9 - Ferreira, M. A. M. (2022)
This book covers key areas of Mathematical Research and Computer Science. The contributions by the authors include relay protection, digital system, ide-area monitoring and control system, local information network, hardware and software reliability and availability, traffic availability, Euler approximation, uniform, error, bound, estimates, stochastic, functional, differential equations, near-duplicate detection, near-duplicates, approximate duplicates, clustering, data mining applications and discovery, data cleaning, complete chaos synchronization, contraction mapping theorem, synchronization threshold, discrete-time dynamical system, synchronized cycles, rime numbers, composite numbers, optical solitons, fractional derivatives, fractional Noether´s theorem, Sub division graph, end edge dominating set, end edge domination numbers, split domination number, deterministic finite automaton, synchronizing word, Cerny conjecture, Weierstrass transform, Weber’s parabolic cylinder function, convergent integral. This book contains various materials suitable for students, researchers and academicians in the field of Mathematical Research and Computer Science